Optimized protocols for RNA-induced silencing complex assembly and cleavage in cultured Drosophila cells - Yajie Gao; Yuanxiang Zhu; Qinmiao Sun; Dahua Chen (STAR Protocols, 2022)
Summary: Here, we provide an optimized RNA-induced silencing complex (RISC) assembly and cleavage protocol in vitro without using radiolabeled RNA. The protocol is useful to characterize the biochemical properties of the RISC. We describe the preparation of RNA probes, the target RNA, and Drosophila cell lysates for RISC assembly assay. We then detail AGO1 complexes immunoprecipitation for RISC cleavage assay. This protocol can detect RISC assembly and cleavage products within 5 days. Moreover, it can detect 5′- and 3′-cleavage products simultaneously.For complete details on the use and execution of this protocol, please refer to Gao et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.